DETEKSI ULKUS DIABETIK DAN PEMERIKSAAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS DI SURAKARTA - M. Mulyaningsih; Sri Handayani (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Diabetes mellitus (DM) is among the top 10 patterns of disease in Surakarta. The prevalence of DM in Surakarta was 5,470 per 100,000 inhabitants in 2018. Dm sufferers can occur neuropathic disorders, structural changes, callus skin protrusions, skin and nail changes, leg wounds, infections and vascular abnormalities. 50% of DM sufferers have a disability in the legs, 24% have peripheral neuropathy and another 11% have peripheral vascular disease. 60% of all patients have a risk of leg ulcers occurring. To do this prevention, it is necessary to detect diabetic foot ulcers and blood sugar levels on a regular basis.Â From the examination conducted to 49 dm sufferers obtained 19 dm sufferers have high blood sugar levels. From the Ankle Brachial Index (ABI) examination there were 4 people with ischemia, and from the examination of foot sensitivity there were 5 people experiencing a decrease in foot sensitivity. Based on the results of the examination, DM sufferers know their blood sugar levels and also know the level of risk of diabetic foot ulcers, so as to take precautions so as not to occur diabetic wounds, especially in the legs.Â Â